Public morality and the culture wars : the triple divide - Fanning, Bryan (Emerald Publishing Limited, 2023)
How is public morality understood in the twenty-first century, and what effect does this have on legislation and social policy? Public Morality and the Culture Wars is a strictly non-polemical analysis of the intellectual and ideological conflicts at the heart of the 'culture wars'. Taking debates on human nature, sexuality, gender identity, abortion, censorship, and free speech, Bryan Fanning offers an accessible analysis of modern public morality, identifying a 'triple divide' between conservative, liberal and progressive viewpoints. A nuanced analysis of 'culture wars' now dividing Anglophone democracies is badly needed. Public Morality and the Culture Wars makes a vibrant and invigorating contribution to the debate, essential reading for scholars and students in the fields of social policy, law, politics, philosophy, sociology and social justice.